2002
DOI: 10.1029/2002eo000031
|View full text |Cite
|
Sign up to set email alerts
|

Mercury on the move during snowmelt in Vermont

Abstract: Although mercury (Hg) emissions peaked in the United States over the last 20 to 40 years and are now declining, they remain well above natural background levels in soils and sediments. Only a small fraction of the Hg deposited from the atmosphere to the terrestrial landscape runs off in streamflow. However, some of this Hg is methylated in the environment and can potentially bioaccumulate to the top of food webs, posing a hazard to people who eat fish, especially children and pregnant women. What factors deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 11 publications
3
66
2
Order By: Relevance
“…However, increases in Hg flux and changes in stream Hg chemistry during high flow events in forested watersheds have been reported elsewhere (Allan and Heyes, 1998;Scherbatskoy et al, 1998;Shanley et al, 2002;Mast et al, 2005). Hg flux was related to particulate organic matter during snowmelt in Vermont (Scherbatskoy et al, 1998;Shanley et al, 2002). The dissolved fraction of Hg, particularly in relation to DOC, also contributes to Hg mobilization during elevated discharge events, including snowmelt 4814 J. T. BUSHEY ET AL.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, increases in Hg flux and changes in stream Hg chemistry during high flow events in forested watersheds have been reported elsewhere (Allan and Heyes, 1998;Scherbatskoy et al, 1998;Shanley et al, 2002;Mast et al, 2005). Hg flux was related to particulate organic matter during snowmelt in Vermont (Scherbatskoy et al, 1998;Shanley et al, 2002). The dissolved fraction of Hg, particularly in relation to DOC, also contributes to Hg mobilization during elevated discharge events, including snowmelt 4814 J. T. BUSHEY ET AL.…”
Section: Introductionmentioning
confidence: 64%
“…Babiarz et al (1998) reported no change in Hg concentrations with discharge during monthly sampling of forested ecosystems in Wisconsin, suggesting that Hg flux was largely a function of discharge. However, increases in Hg flux and changes in stream Hg chemistry during high flow events in forested watersheds have been reported elsewhere (Allan and Heyes, 1998;Scherbatskoy et al, 1998;Shanley et al, 2002;Mast et al, 2005). Hg flux was related to particulate organic matter during snowmelt in Vermont (Scherbatskoy et al, 1998;Shanley et al, 2002).…”
Section: Introductionmentioning
confidence: 64%
“…The long-term data and biogeochemical understanding from nearly two decades of intensive research at these sites provide rich context for the interpretation of Hg behavior. This recent focus on Hg in the WEBB program builds on previous work at three of the sites: Vermont (Shanley et al, 2002;Schuster et al, 2008); Colorado (Mast et al, 2005); and Wisconsin (Krabbenhoft et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…AJES previous studies showed a strong interactions between Hg and DOM have also been indicated by a positive correlation between their concentrations in many natural waters (Andren and Harriss, 1975;Lindberg and Harriss, 1974;Mierle and Ingram, 1991;Meili et al, 1991;Driscoll et al, 1995;Hurley et al, 1995;Watras et al, 1995;Baeyens et al, 1996;Kolka et al, 1999;Shanley et al, 2002).…”
Section: Science Publicationsmentioning
confidence: 99%